The impact of natural virtual environments on perceived restorativeness and individual restoration - Grossi, Elena; Marocco, Silvia (Psychology Hub, 2025)
The literature has long demonstrated the restorative value of natural environments. However, access to these types of environments can often be limited to individuals, for various reasons. In this sense, Virtual Reality (VR) can be a useful tool to promote individual recovery through virtual simulation of natural physical environments. Indeed, it has been shown that nature in VR has regenerative potential comparable to that of physical nature. However, research on the effectiveness of VR nature scenarios remains mixed, necessitating further studies on their validation in terms of restorativeness. The purpose of this systematic review, therefore, was to analyze the current state of the literature on the impact of natural virtual environments on perceived environmental restorativeness and individual restoration, considering the types of natural virtual environments used, the varieties of interventions implemented in these studies and the forms of assessment proposed, and evaluating the final results. It emerges how, over the years, the regenerative potential of various virtual natural environments has been validated. Similarly, different forms of intervention are functional in promoting restoration, although they are little varied concerning the physical location and movement ability of participants during the VR experience. Thus, these findings can be useful for future research on this topic and for the optimization of VR interventions for individual psychological well-being.